Порівняльна характеристика подільського та карпатського фенотипів Helleborus purpurascens Waldst. et Kit. (Ranunculaceae Juss.) в умовах культури - Korotchenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The results of cultivation of Helleborus purpurascens Waldst. et Kit. of Podyllian and Carpathian origin have been analyzed with the purpose to determine differences in the terms of passing through phenological phases of seasonal development.